Issues & Observations How to Put Your Finger on the High Potentials - Berke, David (Center for Creative Leadership, 2003)
In any organization there are individuals who are considered to be the likely future leaders of the organization-in other words, to have high potential for leadership. Developing and retaining these high-potential individuals is crucial to an organization's long-term success. But before high potentials can be developed and retained they must be identified.
Online resource; Title from title page (viewed January 1, 2003)